Edible plant landscaping - Naranja, Leonido R. (UP Los Baños Journal, 2011)
This paper seeks to introduce edible plant landscaping or EPL as a new concept and approach of purposely changing the natural features of a landscape with the desire or intention of making it more attractive and functional. It can also be called edible landscaping. EPL gives primacy to the use of edible plants such as vegetables. fruits, herbs and medicinal plants, thus veering away from the conventional approach that commonly uses ornamental plants. EPL and conventional landscaping both use the same principles and elements of landscape design. Many edible plants possess characteristics and feature similar to ornamental plants used as softscapes in conventional landscaping. These edible plants too, can be used effectively as hedge ground cover, accent or screen. EPL uses unique hardscapes (structures) like trellises and containers to anhance the appearance of plants and to increase their productivity. EPL is offered as appropriate landscaping option for the urban setting characterized as having limited space and stressful environment through creatvie use of materials like containers, trellises, and innovative arrangement and compositions like topiary, espalier, and double pot. It suggest an alternative approach for the orderly and attractive treatment of highways and public parks and other idle lots. The paper also offers a simple assessment of the effort so far done for the promotion of EPL. Finally, it expresses the hope that EPL will gain greater support both from public and private sectors for its further development and wider acceptance and quick adoption by people and communities.